Discrimination in dating apps in the LGBT community: Construction and validation of an instrument - Marroquín Figueroa, Julia María; Esponda Pérez, Jorge Alberto; Juárez Ibarias, Mónica; Tapia de Aquino, Juan Manuel; Sosa Zúñiga, Dolores Guadalupe (Arandu UTIC, 2025)
This study analyzes the Discrimination Scale in LGBT dating apps in adults in Chiapas, Mexico. In this exploratory and psychometric research, 640 members of the LGBT community actively participated. A two-factor structure was validated: individual and group discrimination. When analyzing the frequency of responses for the 17 items, it was observed that items 14 to 16 predominate with responses of “Almost every day”, while for the others, the most common response was “Every day”. In addition, verifying the Cronbach's Alpha values, it is observed that the standardized coefficient is .921, the 95% confidence interval is within the range considered acceptable. These results highlight the ability of the scale to measure this phenomenon in the LGBT community, suggesting its usefulness both in Chiapas, Mexico, and possibly in other similar contexts.